A ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA MATERI OPERASI BILANGAN CACAH KELAS IV SD INPRES 29 KABUPATEN SORONG - Madzkiyah, Azizah Fathanatul; Subanji; Slamet Arifin (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2024)
Learners, especially at the elementary school level, must have mathematical problem solving skills. The purpose of this study is to analyse the ability of primary school learners to solve mathematical problems using the stages of Polya's Theory. This research uses a type of Concurrent Triangulation, which combines quantitative and qualitative methods when collecting data and analysing it. Interviews and written tests were used to collect data. The subjects in this study were fourth grade students of SD Inpres 29 Sorong Regency, Southwest Papua Province with a total of 22 people. The results showed that the problem solving ability of students was still in the low category with details of the acquisition of mathematical problem solving in the high category category 27.27% or 6 students, medium category 31.83% or 7 students, and low category 40.9% or 9 students. In the learning process, teaching materials are needed as well as developing strategies in the learning process that are relevant to the characteristics, environment and needs to support students' mathematical problem solving skills.